Peran Gender, Pendapatan, dan Pendidikan Terhadap Loyalitas Konsumen Yang Berkunjung ke Mall - Tulus Haryono; Dwi Hastjarjo KB (KINERJA, 2010)
This Â study Â was Â meant Â to Â explain Â the Â relation Â between Â relationship marketing, Â consumer Â trust,Â consumer commitment, and consumer loyalty moderated by gender, income, and education. TheÂ data were collected through surveys to consumers loyal to Malls.Â Based on the number of the sample, the tests of sample validity and reliability showed that theÂ result Â was Â that Â the sample Â was Â valid Â and Â reliable. The Â data Â analysis Â was Â carried Â out Â by usingÂ â€œStructural Equation Modelâ€ (SEM).Â The Â findings Â of Â the Â present Â study shows Â that: Â (1) Â there Â is Â a Â positive Â and Â significant Â relationÂ between relationship Â marketing Â and Â  Â consumer Â trust, Â (2) Â there Â is Â a Â positive Â and Â no significantÂ relation between relationship marketing and consumer commitment, (3) there is a positive andÂ significant Â relation Â between Â consumer Â trust Â and consumer Â commitment, Â (4) Â there Â is Â a Â positiveÂ and significant relation between consumer commitment and consumer loyalty, and (5) there is aÂ positive and no significant relation between relationship marketing and consumer loyalty.